Determination of the acoustic properties of Turkish ling six sounds used in speech tests. (3rd July 2022) - Onen, Çigdem; Mengu, Guven; Altinyay, Senay; Kemaloglu, Yusuf Kemal
ABSTRACT: The Ling Six-Sound Test has been determined to be both valid and reliable in relation to the evaluation of hearing using speech sounds. However, prior studies in this regard have principally been conducted in English, and it must be acknowledged that Turkish and English acoustic properties differ from one another. In this study, we sought to determine the acoustic properties of the phonemes that correspond to the Turkish letters [a, u, i, m, s, ş] used in speech tests when evaluating children's hearing. The children are more sensitive to their mother's voice and to their mother tongue. Further, audiology is a female-dominated field in Turkey. Thus, this study was conducted among 51 Contemporary-Turkey-Turkish (CTT)-speaking female subjects who were aged between 18 and 45 years and who were considered normal with regard to their hearing, voice and speech abilities. The participants' acoustic sound analyses were performed using sound analysis software. The frequency ranges within which the Ling sounds were found to have energy at the hearing level were 250–1500 Hz for, 250–1000 Hz for, 250–3000 Hz for, 4000–15, 000 Hz for, 2000–13, 000 Hz for <ş>, and 250–2000 Hz for . When using the Ling sounds to perform hearing assessments and hearing aid/cochlear implant fitting, it is essential to consider the frequency ranges that are specific to each language. In addition, special software and devices need to be developed if the Ling Six-Sound Test is to be applied more quickly and efficiently in the future.